On the modeling of circular piezoelectric transducers for wave propagation-based structural health monitoring applications - Lopes, Kayc W [UNESP]; Gonsalez-Bueno, Camila G [UNESP]; Inman, Daniel J; Bueno, Douglas D [UNESP] (SAGE Publications, 2023)
Structural Health Monitoring (SHM) techniques have an important role in the performance of mechanical structures. In particular, piezoelectric transducers (PZT) have been employed for establishing damage detection processes in SHM systems. However, despite their wide use, there is limited information in the literature regarding important characteristics for SHM applications, such as the shape, dimensions and frequencies to use, which can affect the performance of the system used to detect the damage. This article investigates longitudinal and flexural waves for applications using circular piezoelectric transducers bonded to thin plates. The methodology allows one to obtain optimal frequencies to create and capture both types of waves and understand the influence of the geometric characteristics of these transducers on the damage detection. Numerical simulations are carried out to show that a change in the parameters of the piezoelectric transducers can maximize the waves amplitudes incoming at the sensor. Results from experimental tests are presented to demonstrate the proposed methodology. New equations are introduced and they compute output voltage and determine optimal frequencies to monitor the structure. The findings contribute to establishing a more efficient design of a damage detection process involving plate-like structures in SHM systems based on wave propagation.
Keywords: circular piezoelectric transducer; optimal frequencies; thin plate; Wave propagation